Basic Concepts in Environmental Biotechnology - Sharma, Neetu; Sodhi, Abhinashi Singh; Batra, Navneet (Oxon: CRC Press, 2025)
The book includes current and emerging concepts in the areas of environmental biotechnology such as pollution sources, control and measurement, solid waste management, bioremediation, biofuels, biosensors, bioleaching, conservation biotechnology and more. The book also includes recent innovations made in this field and incorporates case studies to help in understanding the concepts. This book applies principles from multidisciplinary sciences of environmental engineering, metabolic engineering, rDNA technology and omics to study the role of microbes and plants in tackling environmental issues. It also includes content related to risk assessment and environmental management systems. Each chapter provides problems and solutions of different topics with diagrammatic illustrations and tables for students, researchers and other professionals in environmental biotechnology.
Includes Bibliography and index
Keywords: Environmental biotechnology; Bioremediation; Waste disposal$1 (BBiotechnological innovationss; Microbial ecology; Pollution$1 (BBioremediations -- Sustainable development